10 unmalted alternative cereals and pseudocereals: A comparative analysis of their characteristics relevant to the brewing process. (July 2022) - Baillière, Jeroen; Laureys, David; Vermeir, Pieter; Van Opstaele, Filip; De Rouck, Gert; De Cooman, Luc; Vanderputten, Dana; De Clippeleer, Jessika
Abstract: To meet consumer demand and remain competitive, brewers attempt to broaden their product range with new, innovative flavors. One way to achieve this is by (partially) replacing barley malt with less common adjuncts, such as the ancient wheat varieties einkorn, emmer, spelt, and khorasan; the pseudocereals quinoa, amaranth, and buckwheat; or the alternative cereals sorghum, teff, and tritordeum. The physical (grain size and thousand kernel weight), chemical (starch, protein, fat, β-glucan, and water content), and physicochemical (gelatinization temperature, amylase content) properties of these alternative cereals and pseudocereals were determined, as well as their aldehyde concentrations and flavor profiles. The starch content ranged from 45.2 ± 1.2 %dm for einkorn to 75.5 ± 0.6 %dm for teff. The protein content ranged from 10.6 ± 0.0 %dm for barley malt to 18.4 ± 0.6 %dm for khorasan. Major differences were found for the diastatic power, with quinoa having the lowest (6 ± 4 °WK) and spelt the highest (277 ± 19 °WK) value. Most alternative cereals and pseudocereals had an onset gelatinization temperature ≤63 °C, making them suitable for common brewing practices. This was not the case for quinoa, amaranth, teff, and sorghum, which had a gelatinization temperature ≥64 °C. Aldehyde concentrations were significantly lower in alternative cereals and pseudocereals, compared to malted barley. Graphical abstract: Image 1 Highlights: All unmalted alternative cereals and pseudocereals contained more protein than barley and barley malt. High β-amylase activity was found in einkorn, emmer, spelt, Khorasan, and tritordeum. Starch onset gelatinization temperature in quinoa, amaranth, teff and sorghum was >64 °C. All unmalted alternative cereals and pseudocereals contained much less aldehydes than barley malt.